A polymer-supported electrolyte-affinity hybrid membrane and modification of the amphiphilic block copolymer for use as a super-high flexible and high-performance supercapacitor. Issue 5 (4th May 2017) - Zhao, Xiaoning; Yang, Yunlong; Wu, Jiayu; Tan, Yongtao; Liu, Ying; Kong, Lingbin; Kang, Long; Ran, Fen
Abstract : In this study, a super-high flexible membrane electrode (FME) was developed via a facile method based on liquid–liquid phase separation involving the migration and self-assembly of the components. Abstract : In this study, a super-high flexible membrane electrode (FME) was developed via a facile method based on liquid–liquid phase separation involving the migration and self-assembly of the components. Note that the surface segregation and chain orientation of the amphiphilic block copolymer PAA- b -PAN- b -PAA on the membrane surface during the phase separation process provide the hierarchical porous structure and electrolyte-affinity electrode surface; this hierarchical porous structure provides pathways for the electrolyte ions into and from the electrolyte/solution interface for further contact and reaction of the electrochemically active materials with the electrolyte ions. In a three-electrode system, the specific capacitance of FME-Ni(OH)2 can reach up to 2198.6 F g −1 (769.5 C g −1 ) at the current density of 0.5 A g −1 from 0 to 0.35 V as compared to that for non-flexible Ni(OH)2 (1588.6 F g −1 ; 556.0 C g −1 ). Moreover, a flexible asymmetric supercapacitor with FME-Ni(OH)2 as the positive electrode and FME-AC (commercial activated carbon) as the negative electrode showed the high specific capacitance of 102.2 F g −1 (163.5 C g −1 ) and the maximum energy density of 36.3 W h kg −1 at the power density of 400 W kg −1 ; moreover, it retained the energy density of 20.6 W h kg −1 at the high power density of 4000 W kg −1 in the potential window ranging from 0 to 1.6 V in a 6 M KOH aqueous solution.